Regulation of IL-12 Family Cytokines in Normal and HIV-1-infected Human Monocytic Cells - Rahim Rahimi, Ali Akbar (University of Ottawa (Canada), 2010)
HIV infection results in progressive loss of general and HIV-specific cellular immunity. HIV employs a variety of mechanisms to undermine the effectiveness of the host immune system including dysregulation of IL-12 family of Th1 cytokines such as IL-12, IL-23 and IL-27. These cytokines are abundantly produced by monocytic cells following stimulation with various TLR ligands that are components of viruses, bacteria, or microbial products such as LPS and cytokines such as IFNgamma. Monocytic cells in addition to being key sources of Th1 cytokines, act as a bridge between innate and adoptive immune responses and playa crucial role in mv immunopathogenesis. It is well established that IL-12 production by monocytic cells is decreased in HIV-infected individuals and following in vitro infection of monocytic cells with HIV. However, the role played by IL-23 and IL-27 in HIV immunopathogenesis is not clear. Moreover, whether expression of IL-23 and IL-27 is altered in monocytic cells from HIV-infected individuals and following in vitro infection of monocytic cells remains unknown. To understand the molecular mechanisms underlying the loss of protective Th1 responses in HIV infection, it is imperative to investigate the role and regulation of IL-23 and IL-27. Therefore, I have investigated the molecular mechanisms by which LPS alone or in combination with IFNgamma regulate the expression of IL-23 and IL-27 in human monocytic cells and human monocytic cell lines as model systems. I show that LPS-induced IL-23 proteins production is regulated through the activation of JNK, p38 MAPKs and PI3K signalling pathways in THP-1 cells, but following stimulation with IFNgamma and LPS, IL-23 is regulated primarily by the PI3K pathway. In normal monocytes, IFNgamma- or IFNgamma/LPS- induced IL-23 protein production is regulated through the activation of PI3K and calcium pathways. In terms of IL-27 regulation in normal monocytes, I have demonstrated that p38 MAPK and PI3K are the essential signalling pathways that regulate IFNgamma/LPS-induced IL-27 production. Moreover, LPS- and IFNgamma/LPS-induced IL-27 expression is regulated by JNK, p38 MAPKs and PI3K pathways in THP-1 cells. Subsequently, I have elucidated the effects of HIV infection of human monocytes, and monocytic cell line (THP-1 cells) on spontaneous as well as LPS-induced production of1L-23 and IL-27. My results suggest that HIV-infection transiently increases IL-23p19, IL-12/23p40 mRNA and IL-23 proteins, but in terms of IL-27 it only increases IL27EBI3 mRNA expression and does not affect on IL-27 proteins production. In addition, I show that HIV-infection does not affect LPS-induced IL-27 production, but it has a remarkable inhibitory effect on LPS-induced IL-23 production in THP-1 cells and PBMCs. Taken together, this study provides basic understanding of the major signaling pathways involved in the regulation of IL-23 and IL-27 in activated monocytic cells as well as the effects of in vitro HIV infection on the expression of these cytokines. These results may suggest potential strategies aimed at enhancing immune responsiveness.
Keywords: Biology, Microbiology.